Use of tissue specimens from stereotactic biopsies for patient-derived GBM organoid-based drug testing - Wöllner, Amélie; Paul, Adrian; Arquilla, Maddalena; Cao, Junguo; Lotsch, Catharina; Jungwirth, Gerhard; Jassowicz, Lena; Deimling, Andreas von; Unterberg, Andreas; Krieg, Sandro; Jakobs, Martin; Warta, Rolf; et al. (Cells, 2025)
IDH-wildtype glioblastoma (GBM) represents the most common malignant form of brain tumor and is still incurable despite comprehensive therapeutic efforts. Due to tumor location and patient condition, open surgical resection of recurrent GBM is not always feasible. In these cases, frame-based stereotactic biopsies represent a less invasive technique to obtain tissue samples for diagnostics. However, whether this material would also be sufficient to prepare tumor organoids (TOs) and perform drug screenings has not been addressed so far. In this study, we present our highly optimized workflow for generating standardized patient-derived GBM TOs from single-cell suspensions using limited biopsy-derived material. We highlight crucial steps within the procedure, such as reliable cell counting, viable cell recovery, enzymatic digestion, and the requirement of an extracellular matrix as a scaffold. Furthermore, we showcase the potential of personalized drug testing as a promising application of GBM TOs. In conclusion, we successfully developed a robust workflow that effectively utilizes the limited material derived from stereotactic biopsies to reproducibly form standardized TOs. Moreover, we demonstrate that biopsy-derived TOs represent a valuable tool for testing drug vulnerabilities in a personalized setting, which might be especially useful in the case of non-resectable GBM.